Modelos Unifactoriales de Tipos de Interés: Aplicación al Mercado Colombiano (2008)
This article is a first approach to implementing in the Colombian market the unifactorial interest rate models developed by Hull and White (1990) and by Black and Karasinski (1991) with constant volatility and reversion velocity parameters. The main findings from this research are 1) implementing both models using trinomial trees enables accurately replicating the forward structure of market interest rates; 2) the parallel movements of the installment structure of interest rates in Colombia explains most of their variability, thus, using unifactorial models such as the ones proponed herein is appropriate; 3) the volatility and reversion velocity mean parameters on the mean short-term interest rate must be estimated using time series econo-metric models; 4) future articles must broach the problems related to coverage using such types of models, to estimating volatility structures and surfaces, and to multifactorial model calibration.